The Effectiveness of Self-Guided Virtual-Reality Exposure Therapy for Public-Speaking Anxiety - Premkumar, Preethi; Heym, Nadja; Brown, David Joseph; Battersby, Steven; Sumich, Alexander; Huntington, Bethany; Daly, Rosie; Zysk, Eva (Frontiers in Psychiatry, 2021)
Objectives: Self-guided virtual-reality exposure therapy (VRET) is a psychological intervention that enables the person to increase their own exposure to perceived threat. Public-speaking anxiety (PSA) is an anxiety-provoking social situation that is characterized by fear of negative evaluation from an audience. This pilot study aimed to determine whether self-guided VRET (1) increases exposure to PSA-specific virtual social threats, and (2) reduces anxiety, arousal, heartrate and PSA over repeated exposure. Methods: Thirty-two University students (27 completers) with self-reported high public-speaking anxiety attended two weekly self-guided VRET sessions. Each session involved the participant delivering a 20-minute speech in a virtual classroom. Participants were able to increase their exposure to virtual social threat through the audience size, audience reaction, number of speech prompts, and their own salience in the virtual classroom at four-minute intervals. Participants’ heartrates and self-reported anxiety and arousal were monitored during these intervals. Participants completed psychometric assessments after each session and one month later. Results: Participants increased their exposure to virtual social threat during each VRET session, which coincided with a reduction in heartrate and self-reported anxiety and arousal. Improvement in PSA occurred post-treatment and one month later. The in-session improvement in anxiety correlated with reductions in fear of negative evaluation post-treatment and one month later. Conclusions: Increased self-exposure to virtual social threat from self-guided VRET relieves anxiety and shows immediate reductions in subjective and physiological arousal during application, but also yields sustained improvement in PSA.